2018
DOI: 10.3390/jcm7120541
|View full text |Cite
|
Sign up to set email alerts
|

Tarsal Tunnel Mechanosensitivity Is Increased in Patients with Asthma: A Case-Control Study

Abstract: Background: Based on changes in lung function and musculoskeletal disorders in patients with asthma, this study aimed to compare the tarsal tunnel and fibular bone pressure pain thresholds (PPTs) of patients with asthma and healthy matched-paired controls. Methods: A case-control study was performed. One hundred participants were recruited: 50 asthma patients and 50 healthy matched-paired controls. Bilaterally, tarsal tunnel and fibula bone PPTs were registered. Results: Statistically significant differences (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…In studies conducted on diseases that cause widespread chronic pain such as low back pain, knee osteoarthritis, and fibromyalgia, it has been observed that as the severity of pain increases, the balance ability deteriorates, postural stability oscillations increase, and risk of falling and fear of falling increase [ 9 , 11 13 , 28 , 29 ]. Patients with respiratory problems [ 20 , 21 ] and patients with foot problems [ 30 ] have also been shown to have increased fall risk. However, the number of studies looking at this relationship was limited in shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies conducted on diseases that cause widespread chronic pain such as low back pain, knee osteoarthritis, and fibromyalgia, it has been observed that as the severity of pain increases, the balance ability deteriorates, postural stability oscillations increase, and risk of falling and fear of falling increase [ 9 , 11 13 , 28 , 29 ]. Patients with respiratory problems [ 20 , 21 ] and patients with foot problems [ 30 ] have also been shown to have increased fall risk. However, the number of studies looking at this relationship was limited in shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…Literature studies have shown results such as age being associated with the risk of falls, pain in the musculoskeletal system and falls and also a relationship between pain and balance is shown [ 9 , 13 15 , 19 ]. Falls are a great concern for most patient groups, including even patients with respiratory problems, who also experience pain and musculoskeletal disorders which results in increased fall risk [ 20 , 21 ]. However, there is little published research investigating the relationship between different levels of shoulder pain, balance ability, falling risk and fear of falling, involving all age groups diagnosed with musculoskeletal shoulder problem.…”
Section: Introductionmentioning
confidence: 99%
“…These associations could be due to patients with asthma present respiratory alterations 5,6, including a reduced diaphragm contractility which have been linked to chronic ankle instability 14 and consequently high risk of falls 10. Indeed, a recent study has shown the presence of higher mechanosensitivity in the tarsal tunnel of patients with asthma with respect to healthy controls 36. According to this study, the sensitization of the soft tissues of the tarsal tunnel, including the plantar flexor tendons, blood vessels and tibial nerve, could decrease foot dorsiflexion range of motion and stability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to respiratory symptoms, previous studies have reported the presence of pain in asthmatic patients, 5,6 reporting temporomandibular joint and neck pain or tarsal tunnel syndrome as frequent concomitant pathologies. This pain could affect the quality of life of these patients 7 however, and despite its importance, the processes involved in the pain development are unexplored.…”
Section: Introductionmentioning
confidence: 99%